Examining pre-service elementary school teacher beliefs and instructional practices in mathematics class - Yoppy Wahyu Purnomo (International Electronic Journal of Elementary Education, 2016)
The gap between theory and practice has become a critical issue in the effort of improving the learning of mathematics. Beliefs may have been one of the contributing factors to the widening of the gap between theory and practice. Therefore, examining the relationship between beliefs and practices in mathematics is crucial to gain an overview of the preparation of potential teacher candidates and the development of teacher education in the future. This study aims to examine the relationship between beliefs held by pre-service elementary school teachers and the instructional practices in mathematics class. This study employs the case study that focuses on one of the pre-service elementary school teachers who is undertaking practical field experience in the 2015/2016 academic year. The findings of this study indicate that the instructional practices do not necessarily reflect the beliefs that are held. On the other hand, beliefs about the nature of mathematics influence more dominant than the other beliefs against instructional practices.